See the example algorithm below from my course notes, I don't follow the operation counting in the inner loop. Can someone walk me through this step-by-step?
Here's the algorithm:
Algorithm PrefixAverages1(A, n): Input: An integer array A of size n. Output: An array X of size n such that X[j] is the average of A[0] to A[j] Let X be an integer array of size n 1 for j=1 to n-1 do 2 a <- 0 3 for k=1 to j do 4 a <- a + A[k] 5 X[j] <- a/(j+1) 6 return X 7
The solution provided to this sample question uses the following steps to calculate the total cost (in primitive operations*) of the running time of the algorithm:
Operation counting for main body and outer loop:
- $1 + op(outerLoop) + 1$
- $2 + op(outerLoop)$
- $2 + (1 + (B-A + 2)op(j>n-1) + (B-A + 1) * 2 + op(innerLoop))$ where $B = (n-1)$ and $A = 1$
- $2 + 1 + 2n + (n-1) * 2 + op(innerLoop)$
- $1 + 4n + op(innerLoop)$
Operation counting for inner loop:
- $innerLoop = \sum_{j=1}^{n-1} 5j + 7$
- $innerLoop = \left(\sum_{j=0}^{n-1} 5j + 7 \right) - 7$
- $innerLoop = \left(5\sum_{j=0}^{n-1} j + \sum_{j=0}^{n-1}7 \right) - 7$
- $innerLoop = \left(5\sum_{j=0}^{n-1} j + 7n \right) - 7$
- $innerLoop = \frac{5n^2}{2} + 7n - 7$
Then putting the cost of the inner loop and the main body together, the total cost is shown as:
- $\frac{5n^2}{2} + 11n -6$
Specifically I don't follow the operation counting for the inner loop, I understand why there's a $- 7$ added when the sum is changed from $j=1$ to $j=0$. But I don't quite understand the subsequent steps that manipulate the equation.
Source: This is a previous exam paper from my University course.
* List of primitive operations:
- Indexing into an array
- Assignment
- Arithmetic
- Method call
- Following an object reference
- Comparison
- Returning a value
Asked By : conorgriffin
Answered By : FrankW
I'll list the arithmetic rules used in each step. In the following $f$ and $g$ are terms that possibly depend on $i$, while $a$ doesn't depend on $i$.
- has no operations.
- you explained in the question.
- $$\sum_{i=x}^y f+g = \sum_{i=x}^y f + \sum_{i=x}^y g$$ and $$\sum_{i=x}^y af = a\sum_{i=x}^y f.$$
- $$\sum_{i=x}^y a = (y-x+1)a.$$
- is wrong. The correct formula to apply would be $$\sum_{i=0}^y i = \frac{y(y+1)}2,$$ making the result from the question $$x = \frac{5n(n-1)}2 + 7n - 7 = \frac 52 n^2 + \frac 92 n -7.$$
Best Answer from StackOverflow
Question Source : http://cs.stackexchange.com/questions/24526
0 comments:
Post a Comment
Let us know your responses and feedback